From Fancy Blue to Red: Controlled Production of a Vibrant Color Spectrum of Fluorescent Diamond Particles. (7th February 2019) - Dei Cas, Laura; Zeldin, Steven; Nunn, Nicholas; Torelli, Marco; Shames, Alexander I.; Zaitsev, Alexander M.; Shenderova, Olga
Abstract: The current study reports a breakthrough method for production of multicolor diamond particulates using a rapid thermal annealing (RTA) approach with precise temperature and time control, enabling annealing of diamond particulates up to 2100 °C without extensive graphitization. The RTA method generates conditions which allow formation of one‐, two‐, and three‐atom nitrogen complexes with vacancies in electron irradiated type Ib synthetic diamond, providing vibrant luminescence in the red, green, and blue spectral ranges, correspondingly. Controlled and highly reproducible formation of specific color centers previously not possible in type Ib synthetic diamond particles opens new opportunities for particulate diamond in a plethora of fluorescence imaging applications in biological and industrial fields. Abstract : Rapid thermal annealing of irradiated diamond particulates up to 2100 °C provides controlled and highly reproducible formation of specific color centers in type Ib synthetic diamond particles with vibrant luminescence in the red, green, and blue spectral ranges.